Older care home residents’ and their relatives’ knowledge, understanding and views of shift handovers: an exploratory, focused-ethnographic qualitative study using interviews and observations - Jill Manthorpe; Caroline Norrie; Katharine Orellana; Valerie Lipman; Jo Moriarty; Rekha Elaswarapu (BMJ Open)
Objectives To investigate residents’ and relatives’ views and experiences of handovers in care homes. This paper reports residents’ and relatives’ awareness of handovers, knowledge of and views on handover practices and purpose, and views on handover effectiveness. Outcomes, safety and satisfaction in clinical settings are influenced by shift handovers. Despite this link with quality, residents’ increasing support needs and the provision of 24 hours care in care homes for older people, little is known about handovers in these settings from a resident and visiting relative perspective.Setting Five purposively sampled care homes for older people in South East England.Participants Home managers (n=5), residents (n=16) relatives of residents (n=10) were interviewed; residents (n=15) and their interactions with staff were observed during handover periods. Participation was voluntary and subject to consent. Residents were identified by managers as having mental capacity to take a decision about participation which was then assessed. An ethnographic approach to data collection was taken, preceded by an evidence review.Results Shift handovers were largely invisible processes to participating residents and relatives, many of whom had given little thought to handover practice, logistics or effectiveness prior to study participation. Their awareness and understanding of handovers, handover practices, and handover purpose and effectiveness varied. There appeared to be an underlying assumption that administrative procedures in care homes would operate without input from residents or relatives. A small number of residents, however, were highly aware of the routine of handovers and the implications of this for the timing of and response to their requests for care or support.Conclusions The care home setting and perspectives of the effectiveness of handovers may influence awareness of, knowledge of and levels of interest in involvement in handovers.